Behavioural ethograms & social hierarchy of carcharhinus limbatus (blacktip) during a simulated-feeding scenario within South African MPA - Parkes, Candice-Jade (2021)
It has become apparent that elasmobranchs form more complex social organisations than previously thought, and recent improvement of new technologies and analysis has provided valuable information into their social behaviour. Here, a simulated-feeding scenario was utilized to investigate the behaviour of Carcharhinus limbatus within Aliwal Shoal MPA, by defining and testing species-specifics ethograms. Ten behavioural units were identified and grouped in the following categories: i) dominant category: ‘fast turn’, ‘upward swim’, ‘downward swim’; ii) semi-dominant category: ‘parallel swim’; iii) submissive: ‘body tilt’, ‘avoid’, ‘giveway’, follow’; and iv) neutral category: ‘pass’, ‘patrol’. A total of 1014 individual behaviours were recorded, with ‘fast turn’ representing 39% and ‘avoid’ representing 19%. There were 475 dominant displays, 32 semi-dominant, 331 submissive and 176 neutral displays. Ten individuals were successfully identified using photographic-identification of their dorsal fin. The observed sharks were mostly females, with average sizes of 146.3 cm ± 3.088 (e.g. sub-adults). The data indicated that size played a significant role in the position of the individual within the hierarchy, with larger individuals showing more displays of dominance and smaller individuals showing more submissive displays. One particularly large female shark, named ‘Broken Tail’, appeared to be consistently more dominant than the other individuals, with also the highest level of re-sightings over the sample period, and the most displays of dominance (33% of the total). Finally, in the few instances where larger species (e.g. Galeocerdo cuvier or Carcharhinus leucas) were present, the number of blacktip sharks observed appeared to be less. Although the observations in the presence of other sharks were too few for drawing statistically significant conclusions, these preliminary observations suggest interspecific interactions during a simulated-feeding scenario. Given the influence of size and possibly individual behaviour, the observed structure and hierarchy displayed by the blacktip sharks in this study is likely to have further fitness and survival implications that will require further studies.